PURITANISM VALUES AS THE FOUNDATIONS OF AMERICAN INDIVIDUALISM FROM THE PERSPECTIVE OF MATERIALISM - Achmad Faqih (PT. Intelek Cendikiawan Nusantara, 2024)
This paper explores the profound impact of Puritanism on the cultural and societal foundation of the United States, with a focus on its role in shaping individualism and materialism. Originating in England, Puritanism emerged as a reform movement rejecting ecclesiastical hierarchy and emphasizing direct communication with God. Upon migrating to America, Puritans established communities centered on religious freedom, self-reliance, and moral responsibility, significantly influencing democratic ideals and the American ethos of personal autonomy. Through historical records and scholarly works, this study highlights how Puritan spiritual practices transitioned into secular ideals, fostering materialism. The Puritan work ethic, rooted in doctrines of predestination, equated material success with divine favor, a concept persisting in contemporary culture. This paper argues that Puritanism’s emphasis on hard work and moral discipline created a trajectory prioritizing individual achievement and wealth. By examining this transformation, the research sheds light on the legacy of Puritan values in shaping the complexities of American identity, from democratic foundations to materialistic tendencies.